Feeding difficulties among Brazilian children: prevalence and associated factors (Research, Society and Development, 2022)
Objective: to present characteristics related to feeding difficulties (FD) in Brazilian children. Methodology: cross-sectional, observational, descriptive study with a quantitative approach that used a structured electronic questionnaire on FD, management and reaction of caregivers to these difficulties, family repercussions, source of knowledge on the subject and professional approach. Results: one thousand caregivers of children aged between 6 months and 10 years answered the questionnaire in full. FD initially manifested between 1 and 4 years of age in 62% of children. Rejection of trying new foods was the main FD (61%); 65% of the children consumed five or less types of food/day, with cooked foods being preferred by 79%; 33% of caregivers attributed the cause of FD to inadequate examples of family feeding and 32% admitted difficulties in keeping the child focused during feeding. Most caregivers reported that FD don’t affect or have little effect on the family dynamics or child’s school life. Caregivers reported offering another food to replace the refused one (42%), insisting on offering a new food (30%) and seeking guidance from a pediatrician (50%) or nutritionist (28%), who advise repeatedly offering new foods in different forms/preparations (41%); 70% of caregivers maintain appointment with the same pediatrician after diagnosis of FD. As a result of FD, 86% of caregivers fear that their children will develop “low immunity” and become sick. Conclusions: FD in the first years of life is prevalent in Brazil, causing concerns for caregivers of these children.